Integration of insecticides and sex pheromones for management of major insect pests of cotton (Gossypium species) in Madhya Pradesh - GUPTA, M P; SRIVASTAVA, S K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1989-90 and 1990-91 on integrated approach of cotton (Gossypium sp) pestmanagement. Three foliar sprays of insecticides (methyl demeton 0.04%, monocrotophos 0.05% and endosulfan 0.07%)and 6 sprays of insecticides (methyl demeton 0.04%, dimethoate 0.045%, monocrotophos 0.05%, endosulfan 0.07%,tliazophos 0.08% and endosulfan 0.07%), were. integrated with the plantation of synthetic sex pheromones of all 3bollworms (Helicovelpa armigera Hubn., Earias spp and Pectinophora gossypiella Saun.) in less susceptible 'JKH 1'cotton hybrid during rainy (kharif) season at Harda, Madhya Pradesh. With the effective management of major suckingpests and bollworm pests highest seed-cotton yield and net profit were achieved from plots treated with 6 sprays ofinsecticides in integration with sex pheromones of all 3 bollworms followed by 3 sprays in integration with sexpheromones and 6 sprays of insecticides alone. However, the net profits were quite similar in treatments 3 sprays withsex pheromones and 6 sprays in alone. These findings based on multi-dimensional approach may be of great practicalutility in cotton pest management.